2021
DOI: 10.3390/metabo11020087
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of SGLT2 Inhibitors on Lipid Metabolism

Abstract: Sodium glucose co-transporter 2 (SGLT2) inhibitors are effective antihyperglycemic agents by inhibiting glucose reabsorption in the proximal tubule of the kidney. Besides improving glycemic control in patients with type 2 diabetes, they also have additional favorable effects, such as lowering body weight and body fat. Several clinical studies have demonstrated their positive effect in reducing cardiovascular morbidity and mortality. Furthermore, the use of SGLT2 inhibitors were associated with fewer adverse re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 51 publications
1
91
1
2
Order By: Relevance
“…et al, Dapagliflozin significantly reduces seizure activity, both at the electrophysiological and clinical level, in a rat model of epilepsy [ 32 ]. It may be associated with a similar effect of glucose fasting-like metabolic switch as the one observed in ketogenic diets, which in some circumstances also improve brain seizure activity [ 54 ]. There is no clinical data comparing the efficacy of ketogenic diets and dapagliflozin therapy on brain epileptic activity; however, adhering to a ketogenic diet is difficult and has to be closely monitored.…”
Section: Neurological Potential Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…et al, Dapagliflozin significantly reduces seizure activity, both at the electrophysiological and clinical level, in a rat model of epilepsy [ 32 ]. It may be associated with a similar effect of glucose fasting-like metabolic switch as the one observed in ketogenic diets, which in some circumstances also improve brain seizure activity [ 54 ]. There is no clinical data comparing the efficacy of ketogenic diets and dapagliflozin therapy on brain epileptic activity; however, adhering to a ketogenic diet is difficult and has to be closely monitored.…”
Section: Neurological Potential Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…While the therapeutic potential of SGLT2 inhibitors for patients with diabetes and CKD is undisputed, the underlying mechanisms of renal protection remain unclear. The current hypotheses involve metabolic aspects such as changes in lipid metabolism and enhanced ketone body production (Thomas and Cherney, 2018;Szekeres et al, 2021), as well as hemodynamic (Thomson and Vallon, 2021), and hypoxic effects (Packer, 2021) of SGLT2 inhibition. Moreover, the immediate reduction in diabetic glomerular hyperfiltration appears to be a common event in patients on SGLT2 inhibitors and is likely critical for longterm maintenance of GFR and prevention of progressive kidney damage (Kohan et al, 2016;Wanner et al, 2016;Perkovic et al, 2018;Perkovic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EMP is a novel type of antihyperglycemic drug that inhibits glucose reabsorption in proximal renal tubules. In addition to its effects on glycemic status in patients with type 2 diabetes, it contributes to weight loss and body fat reduction (Sun et al, 2020;Szekeres et al, 2021). Recently, clinical trials have reported SGLT-2i had beneficial effects on NAFLD, as evidenced by the remarkably reduced ALT, AST, triglycerides, hepatic insulin sensitivity indices (Ranjbar et al, 2019;Kahl et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium-glucose cotransporter 2 (SGLT2) inhibitors are effective hypoglycemic drugs that function by inhibiting glucose reabsorption in proximal renal tubules. SGLT2 inhibitors improve glycemic status in patients with type 2 diabetes; they also contribute to weight loss and body fat reduction (Szekeres et al, 2021). Multiple studies have reported that SGLT2 inhibitor treatments reduce serum cholesterol and triglyceride (TG) levels (Hayashi et al, 2017;Calapkulu et al, 2019); they also increase lipolysis, liver fatty acid oxidation, and ketogenesis (Osataphan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%